Food independence determinant (Rice) In Supporting The Availability Of National Rice - Kurnia, Lendi Ageng; Iskandar, Deden Dinar (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2019)
In maintaining the stability of national rice availability, 3 supporting aspects are needed, namely increasing domestic rice production, procuring government rice reserves through Bulog and importing rice. The purpose of this study is 1) to find out the factors that influence the availability of national rice, 2) to find out the factors that influence food independence, especially rice. The data used is secondary data sourced from BPS, FAO statistics and IRRI statistics. The research design used in this study is a time series study from 1970-2016. The model used in the study is Least Square (LS). The results of the analysis show partially the availability of national rice influenced by domestic rice production, government rice reserves and rice imports. While the ability of domestic rice production in supplying the availability of national rice, which is represented in the substance of food independence, is influenced by productivity, rice supply stability, price gap of rice / rice and farmers' welfare. However, it is not influenced by the application of appropriate technology (in this case the use of subsidized fertilizer). The conclusion of this study is that the availability of national rice is not only supplied from within the country but must still be supported by the procurement of imported rice. In increasing food independence, productivity must be increased, ensuring that government rice reserves are always available, monitoring the development of rice / rice prices are always stable, and paying attention to the welfare of farmers as the main actors in rice trading. Whereas the government's policy of providing subsidized fertilizers needs to be refined and monitored in the field because so far only serves as a complement in the provision of rice to the community.